Secondary metabolites with antiproliferative effects from Albizia glaberrima var glabrescens Oliv. (Mimosoideae). Issue 17 (2nd September 2017) - Fotso, Ghislain Wabo; Kamga, Justin; Ngameni, Bathelemy; Uesugi, Shota; Ohno, Misa; Kimura, Ken-Ichi; Momma, Hiroyuki; Kwon, Eunsang; Furuno, Hiroshi; Shiono, Yoshihito; Ingrid, Simo K.; Yeboah, Samuel O.; et al.
Abstract: A new 5-dehydroxyflavan, namely Albiziaflavan B or (+)-(2 R, 3 S, 4 R )-3′, 4′, 7-trihydroxy-4-methoxy-2, 3- trans -flavan-3, 4- trans -diol (1) was isolated from the root bark of Albizia glaberrima, together with six known compounds including three flavans: (+)-mollisacacidin (2 ), (+)-fustin(3 ) and butin (4 ); two steroids: chondrillasterol (5) and chondrillasterone (6), and a triterpenoid: lupeol (7 ). The structure of1 was established by detailed analysis of its spectroscopic data, especially 1D and 2D NMR spectra, HRESIMS and CD data. Compounds1 –6 were assayed for their antiproliferative effects on two human cancer cells, HeLa at 50 μM ( n = 2) and HL60 at 20 μM ( n = 2). Compound3 and4 were the most active on HL60 with IC50 of 8.1 and 8.3 μM, respectively. Compound6 was the most active with an IC50 of 4.6 μM on HeLa. Abstract :